Convergence of external and internal stressors on a stress-responsive enhancer of the Sonic hedgehog gene to induce hair disorders - Ziyu Chen; XiaoQi Chen; KaiBin Yang; HouDong Zhou; YaFei Zhang; Zhen Huang; YanDing Zhang; Ralf Paus; ZhiCao Yue (Proceedings of the National Academy of Sciences, 2026)
Mammals are constantly exposed to various stressors of internal and external origin. Though hair follicles (HFs) are exquisitely sensitive to stress, it remains largely unknown how stress-induced responses are linked with the intrinsic regulators of HF growth, cycling, and regeneration. Here, we characterize the long-range enhancer of Sonic hedgehog ( Shh ) gene which encodes a crucial mitogen in the HF, and identify a hair stress-responsive enhancer ( HSRE ) as a unified target on which various internal and external stressors converge. Together with the immediate early gene Early growth response 1 ( Egr1 ), this combination of enhancer and transcription factor mediates hair growth arrest and regeneration defects under several stress conditions, including chemotherapy-induced hair loss, noise-induced hair dystrophy, and retarded hair regeneration in aging and obesity. Under stress, the increased expression of Egr1 suppresses Shh gene expression; however, this suppression does not occur when the HSRE is absent. Furthermore, two chemical agents SR11302 and T-5224 which suppress Egr1 expression both rescued the hair disorders under the various stressors. We propose that an Egr1 – Shh axis integrates distinct stress signals and induces hair disorders via suppression of Shh gene expression, and provide a plausible strategy for therapeutic intervention. Our results establish a paradigm of how stress perturbs organ growth and regeneration through the regulation of key intrinsic morphogenetic factors.